Analisis Kerentanan Bangunan Terhadap Bencana Gempa Bumi Di Kecamatan Gantiwarno Kabupaten Klaten Tahun 2014 - Prayogo, Nivo; , Drs. Ir. Imam Harjono, M.Si (2017)
Earthquake is a disaster that can harm even the casualties and the disaster is hard to predict. Gantiwarno sub-district of Klaten is one area that is prone to earthquakes. Proven on May 27, 2006 Earthquake severely damaged. Purpose of this study include: (1). Knowing the level of vulnerability of buildings due to an earthquake, (2). Shareable Knowing the vulnerability of buildings to earthquakes in the District Gantiwarno, (3). Analyzing the vulnerability of buildings to earthquakes and (4). Analyzing the vulnerability of buildings against damage to buildings that have occurred as a result of an earthquake in the District Gantiwarno. The method used in the form of a survey using primary data includes the observation, recording and retrieval of sample points, and use secondary data as location information earthquake catastrophe. Stratified sampling with purposive sampling method that is proposionaluntuk determine the vulnerability of buildings and to look for damage to buildings and use such maps analysis overlay.Berdasarkan Visual interpretation Geological map obtained two lithological units in District Gantiwarno. Both of these lithologic unit is Alluvial (Qvu) and KeboButkak (Tomk). Aluuvial formations dominated by the host rock cover. KeboButak formations dominated by Tuff, agglomerates, andesite basalt, breccia Andesit.Berdasarkan Interpetasi Quickbird imagery and field observations showed that the type of roofs of residential buildings in the district is dominated by the type of roof Gantiwarno regular village is 48.57%, while the structure of the building is dominated by type structure with a pair of brick reinforced rigid diaphragm (RM2) is 80.95%. RM2 structure type has a score of rapid visual screening for potential seismic hazard ofbuilding a low of below 1.75. This value indicates that this type of structure has a degree of vulnerability RM2 Tinggi.Hasil obtained, among others (1). There are 3 Klas vulnerability of buildings is High, Medium, and Low. (2). Distribution of the vulnerability of buildings spread and in the research area, including High zone.